Ocrelizumab treatment for relapsing-remitting multiple sclerosis after a suboptimal response to previous disease-modifying therapy: A nonrandomized controlled trial. (April 2022) - Weinstock-Guttman, Bianca; Bermel, Robert; Cutter, Gary; Freedman, Mark S; Leist, Thomas P; Ma, Xiaoye; Kile, Deidre; Musch, Bruno; Reder, Anthony T; Wolinsky, Jerry S
Background: Many patients with multiple sclerosis (MS) experience suboptimal disease control despite the use of disease-modifying therapy (DMT). Objective: To assess the efficacy and safety of ocrelizumab (OCR) in patients with relapsing-remitting MS (RRMS) and suboptimal response to prior DMTs. Methods: Patients with RRMS and suboptimal responses (one clinically reported relapse and/or lesion activity) after ⩾ 6 months on another DMT were enrolled. OCR 600 mg was given intravenously every 24 weeks. The primary outcome was no evidence of disease activity (NEDA), defined as the absence of protocol-defined relapse, confirmed disability progression (CDP), T1 Gd-enhancing lesions, and new/enlarging T2 lesions. Results: The intention-to-treat (ITT) population included 608 patients; NEDA was analyzed in a modified ITT (mITT) population ( n = 576 (94.7%)). Over 96 weeks, 48.1% of mITT patients achieved NEDA, and most were free from protocol-defined relapse (89.6%), CDP (89.6%), and T1 Gd-enhancing lesions (95.5%); 59.5% had no new/enlarging T2 lesions. Safety observations were consistent with findings in the pivotal trials. Conclusion: Consistent efficacy of OCR on clinical and magnetic resonance imaging (MRI) disease activity measures and progression was shown in patients with RRMS and a suboptimal response to prior DMTs; no new safety signals were observed.